Innovative Technologies in Physical Education and Their Impact on Developing Students Motor Skills: Systematic Literature Review - Nurlan Bolatuly Omarov; Zhaxybek Zhunusbekov; Iskandar Aliyev (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Innovative technologies in physical education have gained prominence in enhancing motor skill development, offering immersive and interactive learning experiences. these technologies, such as virtual reality (VR), augmented reality (AR), and wearable devices, support skill acquisition by providing real-time feedback and personalized practice.